Challenges for Youth Employment in Pakistan : Are They Youth-Specific? - Hou, Xiaohui (2012)
This paper analyzes the patterns of and the challenges for youth employment in Pakistan and examines whether these challenges are youth-specific. Using the 2005/2006 Labor Force Survey, the analysis includes determinants of unemployment, determinants of working in the formal sector, rate of return on education, and determinants of working hours. The paper finds that many of the challenges to youth employment in Pakistan are not youth-specific. Policies should thus emphasize broader labor market reforms, even in the context of tackling youth employment issues. Still, some challenges are youth-specific, such as a higher youth unemployment rate and insufficient returns to better-educated youth. To address these challenges, more youth-specific interventions are needed.